2016
DOI: 10.1038/srep28043
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Populus hybrid zone along the Irtysh River provides insight into plastid-nuclear incompatibility

Abstract: In plants, the maintenance of species integrity despite hybridization has often been explained by the co-adaption of nuclear gene complexes. However, the interaction between plastid and nuclear sub-genomes has been underestimated. Here, we analyzed the genetic structure of a Populus alba and P. tremula hybrid zone along the Irtysh River system in the Altai region, northwest China, using both nuclear microsatellites and plastid DNA sequences. We found high interspecific differentiation, although the hybrid P. ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
(103 reference statements)
1
11
0
1
Order By: Relevance
“…Cyto-nuclear incompatibilities are also found in plants where chloroplast driven incompatibilities cause reduced hybrid fitness [72,73], which can be remedied by biparental chloroplast inheritance [74].…”
Section: 2) Through Cytonuclear Incompatibilitiesmentioning
confidence: 99%
“…Cyto-nuclear incompatibilities are also found in plants where chloroplast driven incompatibilities cause reduced hybrid fitness [72,73], which can be remedied by biparental chloroplast inheritance [74].…”
Section: 2) Through Cytonuclear Incompatibilitiesmentioning
confidence: 99%
“…5). Это совпадает с данными, полученными ранее при изучении гибридных зон (Lindtke et al, 2014;Christe et al, 2016;Jiang et al, 2016;Zeng et al, 2016).…”
Section: таблицаunclassified
“…However, hybrids of the next generations and backcrosses are not always discarded by natural selection and can be quite abundant in populations (Hersch-Green et al, 2014;Roe et al, 2014;Chhatre et al, 2018). Numerous studies in hybridization zones showed that backcrossing between hybrid plants and those of parental species are common (Christe et al, 2016;Hu et al, 2016;Jiang et al, 2016;Zeng et al, 2016;Vasilyeva et al, 2018). Therefore, the observed hybridization is retrogressive, being accompanied by the gradual transfer of genetic material from one taxon to another across inter-species isolation barriers.…”
Section: Introductionmentioning
confidence: 99%